Effect of Gender on Chronic Intermittent Hypoxic Fosb Expression in Cardiorespiratory-Related Brain Structures in Mice - Baum, David M.; Saussereau, Maud; Jeton, Florine; Planes, Carole; Voituron, Nicolas; Cardot, Philippe; Fiamma, Marie-Noëlle; Bodineau, Laurence (Frontiers in Physiology, 2018)
We aimed to delineate sex-based differences in neuroplasticity that may be associated with previously reported sex-based differences in physiological alterations caused by repetitive succession of hypoxemia-reoxygenation encountered during obstructive sleep apnea (OSA). We examined long-term changes in the activity of brainstem and diencephalic cardiorespiratory neuronal populations induced by chronic intermittent hypoxia (CIH) in male and female mice by analyzing Fosb expression. Whereas the overall baseline and CIH-induced Fosb expression in females is higher than in males, possibly reflecting different neuroplastic dynamics, in contrast, structures responded to CIH by Fosb upregulation in males only. There was a sex-based difference at the level of the rostral ventrolateral reticular nucleus of the medulla, with an increase in the number of FOSB/FOSB-positive cells induced by CIH in males but not females. This structure contains neurons that generate the sympathetic tone and which are involved in CIH-induced sustained hypertension during waking hours. We suggest that the sex-based difference in neuroplasticity of this structure contributes to the reported sex-based difference in CIH-induced hypertension. Moreover, we highlighted a sex-based dimorphic phenomenon in serotoninergic systems induced by CIH, with increased serotoninergic immunoreactivity in the hypoglossal nucleus and a decreased number of serotoninergic cells in the dorsal raphe nucleus in male but not female mice. We suggest that this dimorphism in the neuroplasticity of serotoninergic systems predisposes males to a greater alteration of neuronal control of the upper respiratory tract associated with the greater collapsibility of upper airways described in male OSA subjects.